ANALISIS KESESUAIAN DAN DAYA DUKUNG EKOWISATA PANTAI, SELAM DAN SNORKELING DI PULAU BERHALA KABUPATEN SERDANG BEDAGAI PROVINSI SUMATERA UTARA - Amrullah Angga Syahputra; Yunasfi Djayus; Ani Suryanti (AQUACOASTMARINE, 2016)
This study aims to determine the condition of coral reef ecosystems, suitabilityand carrying capacity of beaches, diving and snorkeling. This study was conducted inNovember-December 2015 in the Berhala Island Serdang Bedagai North SumatraProvince. The data used primary data. The data obtained directly from approximatemeasurement, surveys, observations, interviews with travelers and relevant parties. Thesecondary data is the data obtained from the study of literature and documents relatedagencies. The results showed that the percent coral cover is very appropriate category(S1) by 75%. Suitability shore excursions including highly appropriate category (S1)amounted to 81.19% and the carrying capacity of the region amounted to 382tourists/day. Suitability dive tourism including appropriate category (S2) of 74.07% anda carrying capacity of 494 regional tourist/day. Suitability snorkel tours including highlyappropriate category (S1) of 78.39% and a carrying capacity of 214 regional tourist/day.Keywords: Ecotourism, Fish, Coral Reef, Berhala Island